No fear networking a guide to building connections for the socially anxious professional - Alexis, Michaela (Wiley, 2025)
"Transform your networking experience with No Fear Networking Embark on a transformative journey with No Fear Networking: A Guide to Building Connections for the Socially Anxious Professional, tailored for anyone who's ever felt overwhelmed by traditional networking. Crafted by a formerly agoraphobic LinkedIn guru who became a viral sensation at 30, this guide is an essential toolkit for fostering genuine connections and opening doors to new opportunities. No Fear Networking offers a compassionate approach to networking, addressing the challenges faced by socially anxious professionals through practical, actionable strategies. From understanding the nuances of social anxiety to mastering the art of small talk, this book provides everything you need to network with confidence and still feel like yourself."-- Provided by publisher.